Heat Integration for the Air-Conditioning Application using Waste Heat Recovery in the Cast Iron Industry - Inayat, A. (Italian Association of Chemical Engineering - AIDIC, 2021)
The energy demand in the cast iron industry has been increasing for the past decades. Besides this, there is also high-energy demand for air conditioning, especially in the hot climate of the United Arab Emirates (UAE). Process integration tools can identify and measures the potential of energy saving via Heat Integration. The current paper presented a case study for industrial buildings' cooling demand via absorption chiller utilizing waste heat from a cast iron industry located in the Emirates Industrial Area, Sharjah, UAE. The Heat Integration approach has been applied via Pinch Analysis and Problem Table Algorithm to identify the minimum hot and cold utilities. Hot streams consist of four high-temperature furnaces exit gases. The heat exchanger network has been designed to fulfill the energy requirement using ProSim Simulis Pinch software (version 2.0). The minimum hot and cold utilities were predicted at 8,793 W and 1,600 W. The Pinch Point was found at 30 â¦C with more than 80 of energy recovery. Moreover, the current study can achieve the lowest fuel consumption with fewer emissions, reduced utility consumption, less cost, and superior performance. The paper also includes several recommendations for the improvement of the cast iron industry's overall efficiency. Copyright Â© 2021, AIDIC Servizi S.r.l.